2017
DOI: 10.1038/s41598-017-06227-7
|View full text |Cite
|
Sign up to set email alerts
|

VGLL4 Selectively Represses YAP-Dependent Gene Induction and Tumorigenic Phenotypes in Breast Cancer

Abstract: Members of the mammalian Vestigial-like (VGLL) family of transcriptional cofactors activate genes in response to a wide variety of environmental cues. Recently, VGLL proteins have been proposed to regulate key signaling networks involved in cancer development and progression. However, the biological and clinical significance of VGLL dysregulation in human breast cancer pathogenesis remains unknown. Here, we report that diminished VGLL4 expression, but not VGLL1-3, correlated with both shorter relapse-free surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 51 publications
2
51
0
Order By: Relevance
“…One limitation of our model is that despite the specificity of the TBDs they could cause additional nuclear effects that are not mediated by YAP1/TAZ, particularly the TBD of VGLL4. It has been shown in numerous studies that the main function of VGLL4 in cells is to block the binding of YAP1/TAZ to TEAD transcription factors 21,[38][39][40][41][42] , indicating that TBD-VGLL4 should not have any additional effects than to potentiate endogenous VGLL4-mediated TEAD inhibition. In addition, VGLL4 knockout mice have no reported phenotype on skin development 42 , suggesting that blockage of VGLL4 in keratinocytes might not have any functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation of our model is that despite the specificity of the TBDs they could cause additional nuclear effects that are not mediated by YAP1/TAZ, particularly the TBD of VGLL4. It has been shown in numerous studies that the main function of VGLL4 in cells is to block the binding of YAP1/TAZ to TEAD transcription factors 21,[38][39][40][41][42] , indicating that TBD-VGLL4 should not have any additional effects than to potentiate endogenous VGLL4-mediated TEAD inhibition. In addition, VGLL4 knockout mice have no reported phenotype on skin development 42 , suggesting that blockage of VGLL4 in keratinocytes might not have any functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has implicated that YAP serves an important and multifaceted role in cancer progression, including gastric cancer, pediatric cancer and breast cancer (7)(8)(9)(10). YAP also been demonstrated to be overexpressed in various types of solid tumors, including gastric cancer, pediatric cancer and breast cancer, and its overexpression is associated with tumor initiation, invasion and metastasis (9,11,12).…”
Section: Introductionmentioning
confidence: 99%
“…The K562 cell line was used to demonstrate the immunolabelling of DCTPP1 (Song et al , ) and survivin (Schmidt et al , ), and showed moderate cytoplasmic levels of both. MDA‐MB‐231 cell line was used to demonstrate we could immunolabel DCTPP1 (Song et al , ), while MDA‐MB‐468 was chosen as an immunolabelling control for VGLL4 (Zhang et al , ), but both were negative for the detection of these antigens. Of note VGLL4 was not found in any cell line, MDA‐MB‐231 and MDA‐MB‐468 did not express DCTPP1 or survivin, while each had transcripts from these antigens that were detectable by qPCR.…”
Section: Resultsmentioning
confidence: 99%